2013
DOI: 10.1186/1479-5876-11-132
|View full text |Cite
|
Sign up to set email alerts
|

Id1 enhances human ovarian cancer endothelial progenitor cell angiogenesis via PI3K/Akt and NF-κB/MMP-2 signaling pathways

Abstract: BackgroundEndothelial progenitor cells (EPCs) contribute to tumor angiogenesis and growth. We previously reported that over-expression of an inhibitor of DNA binding/differentiation 1 (Id1) in EPCs can enhance EPC proliferation, migration, and adhesion. In this study, we investigated the role of Id1 in EPC angiogenesis in patients with ovarian cancer and the underlying signaling pathway.MethodsCirculating EPCs from 22 patients with ovarian cancer and 15 healthy control subjects were cultured. Id1 and matrix me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 24 publications
5
32
0
Order By: Relevance
“…We also found that ID1 knockdown suppressed the expression and activity of the matrix metalloproteinases, MMP2 and MMP9, in vitro, suggesting that ID1-KD may protect against angiogenic destruction of the extracellular matrix of regional blood vessels during adjacent and distal invasion and metastasis (29)(30)(31). ID1 knockdown induced suppression of angiogenesis may likely be explained in part by the ID1/NF-κB/MMP-2 or ID1/PI3K/Akt signaling pathways identified in ovarian cancer (32) and integrins (α3, α6 and β1)/laminin adhesion in pancreatic cancer (33).…”
Section: Discussionmentioning
confidence: 63%
“…We also found that ID1 knockdown suppressed the expression and activity of the matrix metalloproteinases, MMP2 and MMP9, in vitro, suggesting that ID1-KD may protect against angiogenic destruction of the extracellular matrix of regional blood vessels during adjacent and distal invasion and metastasis (29)(30)(31). ID1 knockdown induced suppression of angiogenesis may likely be explained in part by the ID1/NF-κB/MMP-2 or ID1/PI3K/Akt signaling pathways identified in ovarian cancer (32) and integrins (α3, α6 and β1)/laminin adhesion in pancreatic cancer (33).…”
Section: Discussionmentioning
confidence: 63%
“…ID1 belongs to the basic helix-loop helix family of genes, which have been detected in multiple malignant tumors. In addition, the expression levels of these genes have been associated with invasive features of cancer (52,53). Increasing evidence has indicated that ID1 is upregulated in HCC samples and induces cellular proliferation.…”
Section: Ar and Inhibitor Of Differentiation 1 (Id1)mentioning
confidence: 99%
“…p38 kinases are a class of mitogen-activated protein kinases, which convert extracellular stimuli into a number of cellular responses, including survival, proliferation, migration and differentiation (52). Deregulation of p38 has been identified to be involved in hepatocarcinogenesis (59,60).…”
Section: Ar Suppresses Hcc Metastasismentioning
confidence: 99%
“…Inhibition of GSK3-β by PI3K/AKT upregulates the expression of hypoxia-inducible factor-1α, inducing VEGF transcriptional activation to promote angiogenesis (17). In early 2013, Su et al (18) reported that PI3K/AKT is mediated by inhibitor of DNA binding/differentiation 1 to enhance endothelial progenitor cell angiogenesis in ovarian cancer. In a study by You et al (19), extracellular signal-regulated kinases and PI3K signaling pathways showed strong involvement in the forkhead box protein C2-mediated angiogenesis process.…”
Section: Evidence and Discussionmentioning
confidence: 99%